Patents and economic development in South Africa: Managing intellectual property rights - Anthipi Pouris; Anastassios Pouris (South African Journal of Science)
Intellectual property rights systems are important policy instruments in the armoury of governments. They have the potential to have favourable or adverse consequences for the relevant national system of innovation, technology transfer, research and development and, eventually, economic growth. Whilst there is a debate related to optimisation of patent systems in the developed world, there is limited debate related to the approaches used in developing countries like South Africa. This article presents an effort to assess whether the South African non-examining patent system makes a contribution or if it is detrimental to the country's development. We found that the current intellectual property rights regime not only fails to support the objectives of the national innovation system but also that it facilitates exploitation by foreign interests and creates substantial social costs. Policy recommendations are provided.